Comparison between intracorporeal and extracorporeal ligations in a laparoscopic ovariectomy model in dogs. Issue 3 (27th February 2021) - Martin, Kyle W.; Karn, Krystina; Mickas, Matthew S.; Fransson, Boel A.
Abstract: Objective: To compare the influence of extracorporeal and intracorporeal ligations on the duration of and complications associated with laparoscopic ovariectomy in dogs. Study design: Prospective randomized experimental study. Animals: Healthy intact female dogs (n = 18). Methods: The left and right ovarian pedicles of dogs undergoing laparoscopic ovariectomy were randomly assigned to intracorporeal (n = 18) or extracorporeal (n = 18) ligation groups. Surgeries were performed by two American College of Veterinary Surgeons (ACVS) diplomates and two ACVS residents. The time required to place extracorporeal and intracorporeal ligations, duration of surgery, and intraoperative complications were compared between ligation techniques. Postoperative complications were recorded. Results: The time required for intracorporeal ligation (17.3 ± 8.7 minutes) did not differ from that required for extracorporeal ligation (15.1 ± 6.1 minutes; P = .38). The total duration of surgery was 102.7 ± 28.7 minutes including portal placement and veterinary student closure of incisions. Ligation of the ovarian pedicle was successful in 16 of 17 dogs. Intraoperative hemorrhage occurred in three dogs, and postoperative complications were noted in three dogs, without apparent difference between ligation techniques. Conclusion: No difference was identified between extracorporeal and intracorporeal ligations of ovarian pedicles. Clinical significance: This study does not provide evidence to support one ligation technique rather than the other.